2016
DOI: 10.5751/es-08698-210333
|View full text |Cite
|
Sign up to set email alerts
|

The pathology of command and control: a formal synthesis

Abstract: ABSTRACT. One of the most important theories in the study of environmental governance and policy is the pathology of command and control, which describes the negative consequences of top-down, technocratic governance of social and ecological systems. However, to date, this theory has been expressed somewhat inconsistently and informally in the literature, even by the seminal works that have established its importance and popularized it. This presents a problem for the sustainability science community if it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 21 publications
0
40
0
1
Order By: Relevance
“…Second, pathway diversity is a quantification of resilience and therefore could be used to design policies to maintain or increase resilience; indeed, we used it to calculate the pathways of greatest resilience in the stylized agricultural examples. Resilience researchers are justifiably wary of general metrics of resilience, for example, because they could lead to top-down control to the detriment of the system that is being managed (Cox 2016), or out of suspicion that any general metric exists that could be usefully applied across the wide variety of contexts and systems in which resilience is used (Quinlan et al 2016). To these concerns, we note that to assess pathway diversity requires a full description (or as full as is available) of the social-ecological system, including alternative options and the consequences of options expressed via feedbacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, pathway diversity is a quantification of resilience and therefore could be used to design policies to maintain or increase resilience; indeed, we used it to calculate the pathways of greatest resilience in the stylized agricultural examples. Resilience researchers are justifiably wary of general metrics of resilience, for example, because they could lead to top-down control to the detriment of the system that is being managed (Cox 2016), or out of suspicion that any general metric exists that could be usefully applied across the wide variety of contexts and systems in which resilience is used (Quinlan et al 2016). To these concerns, we note that to assess pathway diversity requires a full description (or as full as is available) of the social-ecological system, including alternative options and the consequences of options expressed via feedbacks.…”
Section: Discussionmentioning
confidence: 99%
“…General guidelines have been offered for how to build resilience (Biggs et al 2015), global limits have been identified (Steffen et al 2015), and resilience assessments help understand how a particular social-ecological system operates (Sellberg et al 2015). There is understandable reluctance to develop universal measures of resilience given that the features that make social-ecological systems resilient may vary widely (Quinlan et al 2016) and such a measure could lead to top-down control that actually undermines resilience (Cox 2016). In any resilience analysis, the "whom, what, when, where, and why" of resilience must also be considered (Meerow and Newell 2019).…”
Section: Representative Definition Metrics Weaknessesmentioning
confidence: 99%
“…From a relational perspective, groundwater governance mainly depends on knowledge dissemination and controlbased strategies. Control-based approaches are often criticised due to both the negative effects on the social-environmental resilience and the lack of long-term benefits (Mazmanian and Kraft 2009;Cox 2016). Moreover, in our study control-based strategies are strongly limited by practical and economic issues because of the large number Table 4 Results concerning the average influence of the actors, the betweenness and degree centrality, the number of times the actors were mentioned and the difference between the maximum and minimum value of influence assigned to them by different groups of key informants.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of a greater diversity of knowledges and perspectives is recommended in contemporary models for participatory and collaborative governance (Bäckstrand, ; Blaikie et al., 1999; Bremer & Glavovic, ; Carvalho & Fidélis, ; Evans & Pratchett, ; Fazey, Fazey, Salisbury, Lindenmayer, & Dovers, ; Fischer, ; Gibbs, ; Gibson‐Graham, ; Kahane, ; Kemmis, ; van Tol Smit, de Loë, & Plummer, ; among others). Common problems with top‐down “command‐and‐control” and generic approaches include ignorance and disconnection from issues on the ground, particularly where decisions are made at a distance or in dissimilar contexts (Acheson, ; Cox, ; Holling & Meffe, ; Scott, ). Interventions are more likely to be effective if they are locally meaningful and greater feasibility and legitimacy may be generated through public participation, further improving chances of success (Bartel, ).…”
Section: Discussionmentioning
confidence: 99%